2016
DOI: 10.1021/acs.analchem.6b00839
|View full text |Cite
|
Sign up to set email alerts
|

AC Electroosmotic Pumping in Nanofluidic Funnels

Abstract: We report efficient pumping of fluids through nanofluidic funnels when a symmetric AC waveform is applied. The asymmetric geometry of the nanofluidic funnel induces not only ion current rectification but also electroosmotic flow rectification. In the base-to-tip direction, the funnel exhibits a lower ion conductance and a higher electroosmotic flow velocity, whereas in the tip-to-base direction, the funnel has a higher ion conductance and a lower electroosmotic flow velocity. Consequently, symmetric AC wavefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…EFR was first demonstrated using pyramidal pore mica membranes [ 31 , 32 ]. Later studies have shown EFR in conical pore polymeric membranes [ 33 ] and photolithographed nanotunnels [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…EFR was first demonstrated using pyramidal pore mica membranes [ 31 , 32 ]. Later studies have shown EFR in conical pore polymeric membranes [ 33 ] and photolithographed nanotunnels [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The required asymmetry occurs, for example, in nano-funnels, 12 or in tracketched membranes with conical nano-pores, [13][14][15] and, indeed, net ACEO pumping has been demonstrated experimentally for such systems. However, for the concentration polarization to be sufficiently strong, the smallest dimension of the nano-channel cannot be too large compared to the Debye screening length, otherwise the concentration polarization is "suppressed" by electroosmosis itself.…”
Section: Introductionmentioning
confidence: 96%
“…Nanofluidics is a branch of fluid mechanics that deals with fluid flow and transport phenomena through nanoscale geometries and has lots of applications in medicine, biology, genetics, material science, and energy conversion technologies [1][2][3][4][5][6][7][8][9][10]. Electrokinetic phenomena are wildly used in nanofluidic devices to perform many tasks such as generating flow field in nanochannels [11][12][13], transport of ions [13][14][15], and manipulating DNAs in the nanoconfinements [16]. The electrokinetics will also affect cell membrane transport through natural or artificial nanopores created on cell membranes [7][8][9]17].…”
Section: Introductionmentioning
confidence: 99%